Reply to "Comment on "Stratigraphy of the Northern Pulo do Lobo Domain, SW Iberia Variscides: A palynological contribution" by Zelia Pereira et al. (2018) - Geobios 51, 491-506" - Pereira, Zelia (2020)
We acknowledge M. Francisco Pereira, D. Martínez Poyatos, I. Pérez-Cáceres, Cristina Gama and António Azor for the interest shown in our work, and appreciate the chance to clarify a few questions raised by Pereira et al.’s (2018) research. The main aim of Pereira et al. (2018) study was to better constrain the ages of the lithostratigraphic units that make the Northern Pulo do Lobo Domain, SW Iberia Variscides.